Everyone here is lying - Lapena, Shari, 1960- ([New York, NY]: Pamela Dorman Books/Viking, 2023)
Welcome to Stanhope. A safe neighborhood. A place for families. On the surface, William Wooler is a family man. But he's been having an affair, an affair that ended horribly this afternoon. Hours later, William's nine-year-old daughter, Avery is missing. Suddenly Stanhope doesn't feel so safe. Who took Avery Wooler?
Keywords: Missing persons -- Fiction; Fathers and daughters -- Fiction; Truthfulness and falsehood -- Fiction; Thrillers (Fiction); Psychological fiction